PERBANDINGAN AKTIVITAS SISWA DALAM PEMBELAJARAN FISIKA DENGAN MENGGUNAKAN MODEL SNOWBALL THROWING DAN MODEL PEMBELAJARAN LANGSUNG DI SMP NEGERI 15 BANDA ACEH - Novia Riani; Ahmad Farhan; Saminan Saminan (FKIP Unsyiah, 2017)
This research aims to compare student activity in the learning process by using two models of direct instruction model and Snowball Throwing. The approach used in this research is qualitative approach and implemented experimentally. The research data obtained during the learning process in the classroom using student activity observation sheet. This observation is done by observers and researchers themselves. Instrument data collection is analyzed using percentage test. The results show direct learning model: motivation: 69%, visual: 81%, mental: 50%, motor: 50%, writes: 50%. And snowball throwing model: motivation: 100%, visual: 100%, bounce: 94%, motor: 94%, writes: 75%. From this research it can be concluded that the snowball throwing model is better than the direct learning model.